Chemopreventive properties of the bran extracted from a newly-developed Thai rice: The Riceberry - Leardkamolkarn V. (2014)
The potential anti-cancer activity of compounds extracted from Riceberry bran was evaluated in human cancer cell lines (Caco-2, MCF-7 and HL-60). Anti-proliferation and BrdU incorporation assays indicated a time-dose dependent effect of dichloromethane (DCM) and methanol (MeOH) extracts, and that HL-60 was the most sensitive cell. DNA fragmentation assay revealed that both extracts could induce different degrees of apoptosis. The apoptotic induction pathway of each extract determined by flow cytometry and immunoblotting assays revealed various phases of cell cycle arrest with alteration of pro-apoptotic p53, caspase-3, and cyclin proteins. The bioactive compounds in each extract were chemically analysed by GC-MS and LC-ESI-MS/MS. Results revealed the presence of two major anthocyanins, cyanidin-3-glucoside and peonidin-3-glucoside, in the MeOH extract, while the DCM extract contained higher content of plant sterols. The latter constituents are considered the major contributors to apoptotic mechanism in the sensitive cell. These bran products are worth developing into medicinal supplements. © 2010 Elsevier Ltd.